2010
DOI: 10.1159/000321958
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hemoperfusion Using Immobilized Polymyxin B in Patients with Rapidly Progressive Interstitial Pneumonias: A Retrospective Study

Abstract: Background: Rapidly progressive interstitial pneumonia (IP), including acute exacerbation of IP, has a high mortality rate. Direct hemoperfusion with a polymyxin B-immobilized fiber column (PMX-DHP) was recently identified as an effective treatment for sepsis-associated acute respiratory distress syndrome. However, little is known about the effectiveness of PMX-DHP for rapidly progressive IP. Objectives: The present study investigates whether PMX-DHP is safe and effective against rapidly progressive IP. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 93 publications
3
49
0
1
Order By: Relevance
“…Teruya et al described an ADM patient who developed rapidly progressive ILD with elevated anti-CADM-140 autoantibody was successfully treated with PMX-DHP after being resistant to combined steroid and immunosuppressant therapy (18). Hara et al reported that PMX-DHP would be a safe and effective therapy for rapidly progressive ILDs of different etiologies that were resistant to initial high-dose glucocorticoid therapy (8). In addition, Sato et al reported that a patient with severe amiodarone pulmonary toxicity was successfully treated with PMX-DHP and completely recovered (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teruya et al described an ADM patient who developed rapidly progressive ILD with elevated anti-CADM-140 autoantibody was successfully treated with PMX-DHP after being resistant to combined steroid and immunosuppressant therapy (18). Hara et al reported that PMX-DHP would be a safe and effective therapy for rapidly progressive ILDs of different etiologies that were resistant to initial high-dose glucocorticoid therapy (8). In addition, Sato et al reported that a patient with severe amiodarone pulmonary toxicity was successfully treated with PMX-DHP and completely recovered (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which PMX-DHP improves oxygenation in rapidly progressive ILD or acute exacerbations of IPF are unclear, various circulating molecules (i.e., monocyte chemotactic protein 1, metalloproteinase (MMP) -9, tissue inhibitor of MMP-1, neutrophil elastase, and IL-8) were decreased by the treatment (3,8,21). Oishi et al reported that the serum levels of cytokines, IL-9, IL-12, IL-17, PDGF, and VEGF significantly decreased immediately after PMX-DHP (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, direct hemoperfusion with a polymyxin Bimmobilized fiber cartridge (PMX-DHP) has been reported to have a beneficial impact on the respiratory status and long-term outcome of patients with AE-IPF (Seo et al 2006;Abe et al 2010;Enomoto et al 2008;Hara et al 2011). Oishi et al reported that proinflammatory, profibrotic, and proangiogenic cytokines, including TGF-β were eluted from PMX fibers used for the treatment of AE-IPF and suggested that adsorption of such cytokines onto PMX fibers might be one of the mechanisms of action involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite routine use of high dose corticosteroids and immunosuppressive agents, some cases are hard to treat. While some report the efficacy of direct hemoperfusion with a Polymyxin B immobilized fiber column (PMX-DHP) (3,4) and intravenous immunoglobulin (IVIG) (5), the efficacy and the safety of the PMX-DHP and IVIG combination are controversial. We herein report a case of rapidly progressive ILD associated with DM which survived with the administration of PMX-DHP and IVIG in addition to high dose corticosteroids and immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%